IMAGE BUILDING THROUGH PUBLIC RELATION MANAGEMENT : A CASE STUDY ON PRIVATE PRIMARY SCHOOL IN BANTUL - Akhmad Farizal; Dwi Sulisworo; Achadi Budi Santosa (International Journal of Educational Management and Innovation, 2021)
This study aims to 1) explore the process of developing public relation management (PR) implemented by the school to build school image 2) find out the implications of the image built by the school for the school progress, 3) provide the solution for the public relation management to build the image. This study applies a qualitative method with a case study approach at Excellent Elementary School of 'Aisyiyah Bantul, an Indonesian private elementary school. Data collection techniques are done by interviewing and collecting digital documents from the Facebook account and Instagram account. Purposive sampling done in selecting participant and triangulation is used to check the validity of the data. The results illustrate that the school applies public relation management through planned steps; those are: setting goals, organizing teamwork, skill-based task force division, planning strategies, maximizing the use of social media. A school's image has some implications for increasing the number of students, increasing school performance, improving the quality of school staff, expanding the school network, saving promotion costs, and school competitiveness. This study offers a solution in applying public relation by optimizing digital platforms to implement public relation management to build school image.